2019
DOI: 10.5650/jos.ess18212
|View full text |Cite
|
Sign up to set email alerts
|

Short-time Fourier Transform of Free Induction Decays for the Analysis of Serum Using Proton Nuclear Magnetic Resonance

Abstract: Serum is the liquid portion of blood routinely used as a clinical specimen. Serum consists of low-molecular-weight compounds 1 3 , macromolecules and their degradation products 4, 5 , inorganic ions 6, 7 , and water. Hydrogen nuclei in serum play important roles through intra-and intermolecular interactions with other nuclei. Most of the hydrogen atoms in serum are associated with water molecules or proteins. Water molecules form hydrogen bonds with nitrogen and hydrogen atoms in macromolecules and low-molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Methods for 1 H-NMR measurement and FID analysis using STFT are described elsewhere 28 . Briefly, each serum sample (200 μL) was mixed with 400 μL of deuterium oxide ( 2 H 2 O) (ISOTEC, Sigma-Aldrich, St. Louis, MO, USA) and pipetted into a 5-mm (outer diameter) NMR tube (Wilmad-LabGlass, Vineland, NJ, USA) for NMR analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Methods for 1 H-NMR measurement and FID analysis using STFT are described elsewhere 28 . Briefly, each serum sample (200 μL) was mixed with 400 μL of deuterium oxide ( 2 H 2 O) (ISOTEC, Sigma-Aldrich, St. Louis, MO, USA) and pipetted into a 5-mm (outer diameter) NMR tube (Wilmad-LabGlass, Vineland, NJ, USA) for NMR analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Data calculated using STFT were imported into Unscrambler X software (version 10.5; Camo Software AS, Oslo, Norway) for a partial least-squares discriminant analysis (PLS-DA) 28 . All data were transformed using standard normal variates to remove scatter effects, by centering and scaling each individual variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…STFT has the ability to extract time-varying behavior from FIDs, allowing for the analysis of dynamic chemical shifts of atoms in flexible proteins [26]. In addition, it has been reported that STFT can extract T 2 * information from FIDs and improve the results of discriminant analysis [27]. Applying the same idea to covariance NMR [28], T 2 *-weighted covariance NMR improves the sensitivity and resolution of signals based on the difference in T 2 *, determined by dividing each FID in the t 1 dimension of 2D-NMR to create a series of sub-FIDs [29].…”
Section: Introductionmentioning
confidence: 99%